PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL RIAS WAJAH FOTOGRAFI SMK NEGERI 3 PROBOLINGGO - Diajeng Elok Setiti; Faidah, Mutimmatul; Pritasari, Octaverina Kecvara; Megasari, Dindy Sinta (Jurnal Tata Rias, 2025)
Instructional media that meet students' needs have a positive impact on the learning process. Tutorial videos in learning facial makeup photography have become a popular media choice among students. This study aims to determine: (1) the results of developing tutorial video media; (2) student learning outcomes; and (3) student responses to the media. The research was conducted using the 4D R&D model and involved 34 students of grade XI at SMK Negeri 3 Probolinggo as respondents. The results include: (1) the development of learning media through the stages of define, design, develop, and disseminate, which has gone through feasibility testing. The results showed an average score of 3.83 from material experts, 4.43 from media experts, and 4.83 from language experts, all categorized as very good; (2) the cognitive learning outcomes achieved an average score of 84.94, while the psychomotor domain scored an average of 86.05, measured through tests after using the tutorial video; and (3) student responses to the tutorial video reached 88%, indicating that the video is highly suitable as a learning aid for black-and-white facial makeup photography. Based on the validation results from material, media, and language experts, the tutorial video developed through the 4D stages has a very high level of feasibility as a learning medium. Students’ learning achievements, both in cognitive and psychomotor domains, showed improvement with scores exceeding the standard mastery level. Additionally, the student response of 88% indicates that the video tutorial is highly effective and appropriate for use in facial makeup photography learning.Keywords: Media development, Video Tutorial Learning Media, Photography Makeup.